2013
DOI: 10.1021/es401663t
|View full text |Cite
|
Sign up to set email alerts
|

Relative Reactivity of Biogenic and Chemogenic Uraninite and Biogenic Noncrystalline U(IV)

Abstract: Aqueous chemical extractions and X-ray absorption spectroscopy (XAS) analyses were conducted to investigate the reactivity of chemogenic uraninite, nanoparticulate biogenic uraninite, and biogenic monomeric U(IV) species. The analyses were conducted in systems containing a total U concentration that ranged from 1.48 to 2.10 mM. Less than 0.02% of the total U was released to solution in extractions that targeted water soluble and ion exchangeable fractions. Less than 5% of the total U was solubilized via comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 83 publications
(117 citation statements)
references
References 33 publications
5
112
0
Order By: Relevance
“…A recent study further showed that monomeric U(IV) species are more susceptible to oxidation than uraninite. 17 In our recent field study at a mining-impacted wetland in France, we demonstrated that a labile monomeric U(IV)-like species (noncrystalline U(IV) bound to Al−P−Fe−Si amorphous aggregates) was predominant in a U-bearing clay-rich layer within the top 30 cm of the soil. 18 The lability of this U(IV) species resulted in the association of U(IV) with Fe(II) and organic matter colloids in the porewater, which significantly increased U(IV) mobility in the wetland, even though more than 99% of U in the wetland is associated with soil.…”
Section: ■ Introductionmentioning
confidence: 81%
“…A recent study further showed that monomeric U(IV) species are more susceptible to oxidation than uraninite. 17 In our recent field study at a mining-impacted wetland in France, we demonstrated that a labile monomeric U(IV)-like species (noncrystalline U(IV) bound to Al−P−Fe−Si amorphous aggregates) was predominant in a U-bearing clay-rich layer within the top 30 cm of the soil. 18 The lability of this U(IV) species resulted in the association of U(IV) with Fe(II) and organic matter colloids in the porewater, which significantly increased U(IV) mobility in the wetland, even though more than 99% of U in the wetland is associated with soil.…”
Section: ■ Introductionmentioning
confidence: 81%
“…Such U(IV) mononuclear species could either be sorbed to the surface of phosphate as well as silicate minerals, or be bound to organic phosphoryl groups (Alessi et al, 2014b). The major occurrence of such species in lacustrine sediments has important environmental implications since mononuclear U(IV) species are potentially more labile than uraninite (Cerrato et al, 2013;Alessi et al, 2014a) and polymerised non-crystalline U(IV) phosphate phases (Alessi et al, 2014b). Such lability raises issues concerning the long term fate of the mononuclear U(IV) species, especially when subjected to sharp redox changes, for example in sediment remediation strategies as dredging operations.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Only a few studies, however, have examined the reactivity of biogenic noncrystalline U(IV) in laboratory systems. 16,17 Alessi et al 16 showed that the noncrystalline U(IV) fraction can be selectively extracted from a U(IV)−U(VI) mixture by an anoxic 1 M bicarbonate solution. Cerrato et al 17 further demonstrated that the U(IV) species can be readily oxidized by dissolved oxygen (DO) and persulfate.…”
Section: ■ Introductionmentioning
confidence: 99%